ATTITUDES OF FOOTBALL FANS TOWARD SOME OF THE MORE CONTROVERSIAL ISSUES SURROUNDING THE GAMES NOWDAYS - Molnar Slavko,; Stevo Popović,; Dragan Radovanović, (Sport Scientific And Practical Aspects, 2025)
The survey, based at attitudes of football fans who lives in towns and cities across Serbia, looked at such areas as the cost of attending matches and how this contrasted with fans' views about player wages. The sample included 219 male students from Faculty of Sport and Physical Education at University of Novi Sad. The criteria for selecting of respondents for the sample were as follow: being a regular student one year at least and attending the classes constantly. For the data collecting was used the technique of survey investigation. The data obtained in the research were processed using the application statistics program SPSS 15.0 by frequency distribution. The results of this investigation were fairly evenly divided between those who have positive attitude and who have negative attitudes toward some of the more controversial issues surrounding the games nowdays.